An External Gear Pump with Axial Stepped-gear Structure and Without Additional Trapped-oil Relief-grooves - Wang Hao; Song Anran; Li Yulong (Jixie chuandong)
In order to solve the problems in the existing gear pump with another trapped oil buffer groove, an external gear pump with axial stepped-gear structure for realizing two different contact ratios is proposed; the trapped-oil load flow from the gear section with a contact ratio greater than 1 is balanced by the trapped-oil relief flow from the gear section with a contact ratio equal to 1, and the trapped-oil phenomenon will be fully alleviated; then the relief gap from the gear section with a contact ratio equal to 1 is calculated by 3D feature method, and the trapped-oil pressure formula is derived by making the trapped-oil load flow equal to the trapped-oil relief flow; finally, an example is demonstrated and validated by PumpLinx software. The results show that the flexible adjustment of the two section gear width ratio makes up for the shortage of the non-adjustable buffer capacity of the existing buffer groove, and has strong applicability to working conditions; the trapped oil pressure formula considering cavitation pressure corrects the negative pressure when the trapped oil expands, which is applicable to the trapped oil pressure calculation under any structure. It is concluded that the pump can effectively alleviate the trapped-oil phenomenon, doesn't need another buffer groove, has simple structure and is convenient for processing.